(3GdLGeY aj GdTQM TQM GdJMQjQs - (3CHh GdMSf RjO Hf eMeOs; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3HGH UaI GdUdGI , hPcQ aQhVgG hSffgG eGjSJHGM ajgG s
(3BNQgG (B:s
(3bGd bGd QShd Gddg Udi Gddg Ydjg (B: (3dGJLUUhG GdbHhQ , hdG JHfhG YdjgG , hdGJbYOhG YdjgG Je GdLRA GdKGfi s
(3cJHJ gPg GdfSNI HQSe NRGfI eMeO Hf CejQ GdeDefjf GdeJhcd Ydi Gddg Hf jMis
(3cJHJ GdYfhGfGJ HNW ehLhOGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3abg GdePGgH GdCNQis